COVID-19 and Its Influence on Selected Employment Relationship Issues - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha (Walter de Gruyter GmbH, 2021)
This chapter discusses the selected issues of employment law arising from the current COVID-19 pandemic, which a prudent employer would take to withstand its harsh business impact, namely, the pay-cut, flex-work arrangement, and retrenchment of surplus labour, among others. In relation to retrenchment, it is worthwhile mentioning that in Malaysia, the terms “retrenchment”, “termination”, and “lay-off” are used interchangeably.1 These terms, however, have different meanings. At the outset, it must be noted that all retrenchments are terminations, but all terminations are not retrenchments. When an employee is retrenched, this amounts to a termination of his services. But when it is said that an employee has been terminated, it cannot only mean that he is retrenched because retrenchment is one method in which an employee’s services can be terminated.